The velveteen rabbit, or, How toys become real - Bianco, Margery Williams, 1881-1944 (Doubleday Books for Young Readers, 2022)
The threadbare Velveteen Rabbit is saved from peril when he is whisked away by a fairy to the idyllic world of Rabbitland, where he learns what it means to be loved.